Bioreactors for Microbial Biomass and Energy Conversion (Green Energy and Technology,, 2018)
This book discusses recent trends and developments in the microbial conversion process, which serves as an important route for biofuel production, with particular attention to bioreactors. It combines microbial conversion with multiphase flow and mass transfer, providing an alternative perspective for the understanding of microbial biomass and energy production process as well as enhancement strategy. This book is relevant to students and researchers who work in the fields of renewable energy, engineering and biotechnology. Policymakers, economists and industry engineers also benefit from this book, as it can be used as a resource for the implementation of renewable energy technologies.